Antología crítica del cuento hispanoamericano del siglo XX (1920-1980) - José Miguel, comp. Oviedo (El libro de bolsillo)
vol. 1. César Vallejo. Roberto Arlt. José María Arguedas. Enrique Amorín. Manuel Rojas. José Luis González. Carlos Martínez Moreno. Mario Benedetti. Jorge Edwards. Julio Ramón Ribeyro. Macedonio Fernández. Pablo Palacio. Felisberto Hernández. Jorge Luis Borges. Adolfo Bioy. Virgilio Piñera. Juan José Arreola. Augusto Monterroso. Salvador Garmendia.